Recent advances in the chemistry of ketyl radicals. (23rd March 2021) - Péter, Áron; Agasti, Soumitra; Knowles, Oliver; Pye, Emma; Procter, David J.
Abstract : Ketyl radicals are valuable reactive intermediates for synthesis. This review highlights exciting recent developments in the chemistry of ketyl radicals by comparing contemporary and more classical approaches for their generation and use. Abstract : Ketyl radicals are valuable reactive intermediates for synthesis and are used extensively to construct complex, functionalized products from carbonyl substrates. Single electron transfer (SET) reduction of the CO bond of aldehydes and ketones is the classical approach for the formation of ketyl radicals and metal reductants are the archetypal reagents employed. The past decade has, however, witnessed significant advances in the generation and harnessing of ketyl radicals. This tutorial review highlights recent, exciting developments in the chemistry of ketyl radicals by comparing the varied contemporary – for example, using photoredox catalysts – and more classical approaches for the generation and use of ketyl radicals. The review will focus on different strategies for ketyl radical generation, their creative use in new synthetic protocols, strategies for the control of enantioselectivity, and detailed mechanisms where appropriate.